TEACHER ROLE OF GUIDANCE AND COUNSELLING IN FIGHT IN JUVENILE DELINQUENCY SMP STATE 7 PADANGSIDIMPUAN - Khairul Amri (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
SMP Negeri 7 Padangsidimpuan City is an educational institution located in the village of Pokenjior Angkola Julu Padangsidimpuan City, which has the vision and mission to build and create a good student, intelligent and accomplished. The vision of the City Padangsidimpuan SMP Negeri 7 learners are creating intelligent, faithful, noble character and skilled, as well as physically and mentally healthy. As its mission of implementing the learning process effective and efficient, improve the ability of educators of educational personnel, improve achievement in the field of sports and the arts, improve penhargaan faith and piety, improving the quality of graduation, increase knowledge about the culture of the area in particular and culture in general. The problem in this research is how the role of Master of Guidance and Counseling to Address Delinquency In SMP Negeri 7 Padangsidimpuan. The purpose of this study was to determine how the role of Master of Guidance and Counseling to Address Delinquency In SMP Negeri 7 Padangsidimpuan and to find out what are the problems faced by the Master of Guidance and Counseling to Address Delinquency In SMP Negeri 7 Padangsidimpuan. Based on the research role of guidance and counseling teacher at SMP Negeri 7 Padangsidimpuan that provide the maximum service to the student, giving direction, creating a discussion group to discuss the things that cause juvenile delinquency and provide guidance and counseling services to students. As well as the problems faced by teachers occur guidance and counseling to address juvenile delinquency is like smoking, pull, fight, skip school and do not go in during study hours.